PROFESIONALITAS GURU SD DAN SMP DI PEDALAMAN SUKU TENGGER - Utomo, Sugeng; Hamid B., Abdul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
The purpose of science, technology, and art for the community are to overcome the problems faced by teachers in Elementary School, Junior High School in the hinterland Tengger Village Ngadas and Junior High School PGRI in the District Poncokusumo Malang Regency, namely; (1) the quality of learning is still below the standard (2) the mastery of teachers in the field of computer programs such as Microsoft word and excel is still low, and (3) Teachers found difficulty in drafting proposal of Classroom Action Research and writing scientific articles. To overcome these problems, then the training: 1) the computer applications with Microsoft Office and Excel programs, (2) the preparation proposal of Classroom Action Research, and (3) the writing of scientific articles. The expected target is teachers able to master information technology, writing scientific papers in the form of Classroom Action Research and scientific articles that can be published so as to improve the professional quality of teachers in the quality of education in the interior Tengger Tribe in particular and District Poncokusumo generally. The results that have been achieved from science, technology, and art are (1) The teachers are able to operate Microsoft Word and Excel well and understand the type and function of Microsoft Word and Excel icons, (2) The teachers can prepare the proposal of Classroom Action Research and scientific articles that can be published.